Pengembangan Modul Pembelajaran Electric Power Steering (EPS) untuk Meningkatkan Pendidikan Vokasi di Bidang Teknologi Otomotif di Politeknik Negeri Malang - Agus Dwi Putra; Diama Rizky Septiawan; Rizkyansyah Alif Hidayatullah; Nicko Nur Rakhmaddian; Faqih Fadillah; Winda Andrini Wulandari (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Informatika Indonesia Surabaya, 2026)
The automotive industry is rapidly evolving with the adoption of advanced technologies, one of which is Electric Power Steering (EPS). EPS technology replaces traditional hydraulic steering systems with an electric system that is more efficient, precise, and environmentally friendly. However, the lack of structured learning modules and teaching materials on EPS poses a challenge in vocational education within the automotive field. This community service program aims to develop a comprehensive learning module that includes the fundamental theory of EPS, practical procedures using the EPS engine trainer, jobsheets for practical activities, and troubleshooting and maintenance guidelines for EPS systems. The module is designed to enhance the understanding of students, the skills of technicians, and to support lecturers in delivering the material effectively. Through a trial run at the Automotive Electrical Engineering Study Program at Politeknik Negeri Malang (POLINEMA), the developed module successfully improves the quality of learning and helps students master EPS technology. Evaluation results indicate that the module effectively aids students in better understanding EPS concepts and performing practical procedures in a systematic manner. It is expected that this module will serve as an important reference in vocational automotive education in Indonesia, especially in response to the ongoing advancements in automotive technology